2020
DOI: 10.1371/journal.pntd.0008666
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite interactions: Leishmania, microbiota and Lutzomyia longipalpis

Abstract: The microbial consortium associated with sandflies has gained relevance, with its composition shifting throughout distinct developmental stages, being strongly influenced by the surroundings and food sources. The bacterial components of the microbiota can interfere with Leishmania development inside the sandfly vector. Microbiota diversity and host-microbiota-pathogen interactions regarding New World sandfly species have yet to be thoroughly studied, particularly in Lutzomyia longipalpis, the primary vector of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 58 publications
2
27
0
Order By: Relevance
“…An Erwinia species from D. radicum larval gut is highly resistant to isothiocyanate compounds [ 53 ], which are toxic to herbivorous insects [ 54 ] and are emitted by plants as a defense [ 55 ]. While Erwinia protect Lutzomyia longipalpis sandflies against parasitism by Leishmania [ 56 ], they are on the contrary pathogenic for their pea aphids hosts Acyrthosiphon pisum [ 57 , 58 ]. Similarly to our study, Wolbachia and Erwinia seem strikingly unable to cohabit in pea aphids [ 59 ] or in D. radicum adult flies [ 32 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An Erwinia species from D. radicum larval gut is highly resistant to isothiocyanate compounds [ 53 ], which are toxic to herbivorous insects [ 54 ] and are emitted by plants as a defense [ 55 ]. While Erwinia protect Lutzomyia longipalpis sandflies against parasitism by Leishmania [ 56 ], they are on the contrary pathogenic for their pea aphids hosts Acyrthosiphon pisum [ 57 , 58 ]. Similarly to our study, Wolbachia and Erwinia seem strikingly unable to cohabit in pea aphids [ 59 ] or in D. radicum adult flies [ 32 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of the seven other bacteria negatively correlated to Wolbachia infection was far less drastically impacted than that of Erwinia , and these bacteria often play positive roles in their insect hosts. The Bacilli Staphylococcus reduces parasitism by Leishmania in sandflies [ 56 ] and also frequently occurs in the order of Lepidoptera, where it may overcome plant protease inhibitor defenses [ 14 ]. The Bacteroidia Flavobacterium helps digesting plant material by producing cellulase in three phytophagous insect species [ 52 ] while Sphingobacterium induces resistance against fungal infection in Delia antiqua larvae [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent 16S rRNA sequence profiling of the gut microbiota from Lutzomyia longipalpis, the primary vector of VL in Brazil, revealed 13 distinct bacterial genera (Bacillus, Enterococcus, Erwinia, Enterobacter, Escherichia, Klebsiella, Lysinibacillus, Pseudocitrobacter, Providencia, Pseudomonas, Serratia, Staphylococcus, and Solibacillus) (Campolina et al, 2020).…”
Section: Sandfly Vector Transcriptomicsmentioning
confidence: 99%
“…Several studies with phlebotomines from America have also demonstrated the importance and potential role of intestinal microbiota in susceptibility and competence in developing Leishmania infection [2]. Recently, in vivo trials of Lutzomyia longipalpis coinfection with different Leishmania species and bacterial isolates (Lysinibacillus, Serratia, and Pseudocitrobacter) reported significant differences, suggesting a powerful effect on inhibiting Leishmania survival, and causing the death of promastigotes in a few hours or days [4]. Other studies showed that bacterial richness and diversity progressively decreased in Leishmania infantum-infected sand flies as the parasite numbers increased [3].…”
Section: Introductionmentioning
confidence: 99%